(3JQGLe HYV CYjGf eOjfI BeOs - (3GdMdHj, eMeO cGeds ((3GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg efRd GdcJGH agPg YLGdI hVYJgG aj JQGLe HYV CYjGf JQTaJ Hge eOjfI BeO LeYJgG ef GdcJH GdJGQjNjI GdJj CPcQgG Mjf YRhj EdjgG hbO UOQJgG HJQLeI MVQI UGMH GdSYGOI Ydj CejQj CafOj OaJQ OGQ hdGjJfG s
(3BNQgG (B:s
( (3CSeGA hdO fRGQ (B) (3bGd CHh YHO Gddg eMeO Hf YHO GdSdGe GdNTfj deG GMJVQ fRGQ Hf eYO Hf YOfGf JQc CQHYI Hfjf eVQ hQHjYI hCfeGQ hEjGO hChUi Cf jbSe ejQGKge Hjfge SWjM GdcGgf aeG eGJ fRGQ Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJGQjNs